PENGARUH PEMBERIAN AIR REBUSAN JAHE TERHADAP PENURUNAN TEKANAN DARAH PADA LANSI HIPERTENSI DI KORONG GADANG RW 06 WILAYAH KERJA PUSKESMAS KURANJI PADANG TAHUN 2023 - Madoni, Abri; Cleodora, Cindy; Hutabarat, Kristin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
West Sumatra, the incidence of hypertension in the elderly is still high, ranking second (7.562) and the 10th most common disease. Treatment of hypertension can also be done with non-pharmacological therapy, one of which is ginger boiled water. The purpose of this study was to determine the effect of ginger boiled water on reducing blood pressure in the elderly with hypertension in Korong Gadang Rw 06, Kuranji Padang Health Center Working Area in 2023. This type of research is a Quasi Experiment with one group pretest – posttest design. The population of this study was the elderly with hypertension in the Working Area of Kuranji Padang Health Center with a sample of 10 people. Data processing is editing, entry, and cleaning. Univariate analysis using descriptive statistics bivariate analysis using paired T-test. The results showed that the average blood pressure before giving ginger boiled water was 162,50/101,00 mmHg. While the average blood pressure after giving ginger boiled water was 142,00/91,50 mmHg. The paired T-test results obtained a p-value of 0,000 which means that there is an effect of giving ginger boiled water on reducing blood pressure in hypertensive elderly. Through theleadership of the Kuranji Health Center the provision of ginger boiled water can be included in the puskesmas program as a nonpharmacological treatment that can have a positive effect on lowering blood pressure.Keywords: Hypertension, Ginger boiled water, Blood Pressur